A Comprehensive Review of Literature on the Dynamics of Islamic Finance: Global Growth and Challenges - Posumah, Nurcahya Hartaty (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Islamic financial markets have become an important subject in global economic discussions, with significant growth in recent decades. Factors such as awareness of sharia principles, product innovation, quality financial regulations, Islamic financial literacy, and cooperation between countries have played an important role in strengthening the Islamic financial market. This research investigates the relationship between these factors and the growth of the Islamic financial market as a whole.